INTERNATIONAL GOVERNMENT SECURITIES: SPECIFIC FUNCTIONING - N. Versal (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
It’s disclosed the features of the international government securities market during 1993 – 2012: main players are the developed countries (Western Europe, Canada, USA) with the increasing role of developing countries; debt crises have the negative impact as on the development of the international government securities market, but also on the international capital market as a whole; debt crises are not a spontaneous phenomenon, and usually occur as a result of inadequate growth in GDP increasing government debt.